J. Perry Lewis. Urban economics, a set approach, London. Edward Arnold Publishers, 1979. - Ibarra Vargas, Valentín (El Colegio de México A.C., 1981)
J. PERRY LEWIS, Urban economics, a set approachy, London. Edward Arnold Publishers, 1979.